Sugar and Space? Not the Case: Effects of Low Blood Glucose on Slant Estimation are Mediated by Beliefs. (May 2013) - Shaffer, Dennis M.; McManama, Eric; Swank, Charles; Durgin, Frank H.
There is a current debate concerning whether people's physiological or behavioral potential alters their perception of slanted surfaces. One way to directly test this is to physiologically change people's potential by lowering their blood sugar and comparing their estimates of slant to those with normal blood sugar. In the first investigation of this (Schnall, Zadra, & Proffitt, 2010 ), it was shown that people with low blood sugar gave higher estimates of slanted surfaces than people with normal blood sugar. The question that arises is whether these higher estimates are due to lower blood sugar, per se, or experimental demand created by other aspects of the experiment. Here evidence was collected from 120 observers showing that directly manipulating physiological potential, while controlling for experimental demand effects, does not alter the perception of slant. Indeed, when experimental demand went against behavioral potential, it produced judgmental biases opposite to those predicted by behavioral potential in the low blood sugar condition. It is suggested that low blood sugar only affects slant judgments by making participants more susceptible to judgmental biases.